Bonebridge implantation for mixed hearing loss in a patient with Kabuki syndrome - Pepe, Giovanni; Negri, Maurizio; Falcioni, Maurizio; Di Lella, Filippo; Vincenti, Vincenzo (Acta Biomedica Atenei Parmensis, 2020)
The high prevalence of middle ear disease with related hearing loss in Kabuki syndrome requires the diagnostic and treatment expertise of otologists. This case report describes outcomes and changes in the quality of life of a patient affected by Kabuki syndrome with a history of recalcitrant chronic otitis media and mixed hearing loss who had undergone several unsuccessful surgical procedures before solving his problems by means of subtotal petrosectomy and active middle ear implant.